Successful Treatment of Respiratory Failure in a Patient with Prader-Willi Syndrome with Noninvasive Ventilation with AVAPS - Nauras Hwig; Montserrat Diaz-Abad; Victor T. Peng; Jennifer Y. So; Anayansi Lasso-Pirot (Case Reports in Medicine)
Prader-Willi syndrome (PWS) is the most prevalent syndromic form of obesity, which starts during early childhood in the setting of hyperphagia. Due to the development of obesity, there is a high prevalence of obstructive sleep apnea (OSA) among these patients. This case report presents a patient with PWS with morbid obesity, severe OSA, and obesity hypoventilation syndrome admitted to the hospital for hypoxemic and hypercapnic respiratory failure. Noninvasive ventilation (NIV) with average volume-assured pressure support, a newer NIV modality, was used successfully to treat this patient, achieving major clinical and gas exchange improvement both during the hospitalization and long term after discharge.